PENGARUH CORPORATE GOVERNANCE TERHADAP INVESTMENT EFFICIENCY DENGAN INDUSTRY COMPETITION SEBAGAI VARIABEL MODERASI - Fenny Luo; Elsa Imelda (Jurnal Paradigma Akuntansi, 2026)
This study aims to determine the effect of corporate governance on investment efficiency and the role of industry competition in financial sector companies that got into the top three categories of Indonesia’s Most Trusted Company Award from the Indonesian Institute for Corporate Directorship in the years between 2015 and 2021. This research uses the financial reports of 29 companies as secondary data samples, selected using the purposive sampling method and examined using multiple regression analysis and moderated regression analysis assisted by the SPSS 26 program. The results of this research indicate that there is no significant effect that corporate governance has on either investment efficiency, overinvestment or underinvestment. Furthermore, the moderating role of industry competition is proven to strengthen the effect that corporate governance has on investment efficiency. The implication of this study is the need to improve the role of corporate governance to increase the efficiency of every decision made by the agents and increase the awareness of the investors of the need to take a company’s industry competition level as a point to consider before making the decision to invest in that company.